History of menstrual disorders associated with gestational diabetes mellitus - Shahnaz Barat; Zinatossadat Bouzari; Shahla Yazdani; Rahil Moslemi; Karimollah Hajian-Tilaki (Babol University of Medical Sciences, 2016)
Background: Despite the fact that many studies have been published about the risk factors associated with gestational diabetes mellitus, its prevalence remains high. The aim of this study was to examine the relationship between the history of irregular menses and gestational diabetes mellitus among pregnant women. Methods: This case-control study was conducted on 51 pregnant women with gestational diabetes mellitus in prenatal clinics of Ayatollah Rouhani hospital in Babol, Mazandaran, from January 1, 2014 to December 31, 2015. At first, women with family history of diabetes mellitus, pre-pregnancy diabetes mellitus, previous gestational diabetes mellitus, age >35 years, weight >110 kg were excluded from the study. Then, one random control was systematically selected for each case, which was matched for age. All statistical analyses were performed through SPSS (Version 22).  P-values less than 0.05 were considered statistically significant. Results: Irregular menses was not associated with gestational diabetes. The mean menarche at age was lower among the women with gestational diabetes (p=0.03). There was a significant association between menarche at age and gestational diabetes (OR, 6.74; 95% CI, 1.41-32.17). Dysmenorrhea did not differ between subjects with and without menstrual irregularities. Conclusion: We concluded that early menarche at age (<12 years) could be an important consideration for obstetricians, who adopt a selective screening approach to gestational diabetes.